POLA PERTUMBUHAN KERANG AIR TAWAR (Margaritifera sp) DI SALURAN IRIGASI DESA SAMBORA KECAMATAN TOHO KABUPATEN MEMPAWAH - Fenti Fenti; Ahmad Mulyadi; Sri Rahayu (Jurnal Sains Pertanian Equator, 2020)
Margaritifera sp shells can be found in the irrigation channel of Sambora Village. Clams are filter feeders groups or animals that take food by filtering water. The irrigation water flow in Sambora Village contains a substrate of muddy sand and sandy mud. This research aims to determine the morphometric characteristics and growth patterns as well as density of shells in the irrigation channel of Sambora Village, Toho Sub-district, Mempawah District. It used a purposive random sampling method. This research was conducted in March-May 2020 and the research location was divided into 3 stations. It found a total of 801 Margaritifera sp shells. All characteristics of average shell length (PC), shell height (TC), shell thickness (TBL), and total weight (BT) showed varying sizes between males and females in which the female has greater sizes than the male. The relationship between shell length and the total weight is in the range of b <3 which shows a negative allometry growth pattern. The density values ranged from 1.22 - 3.02 ind/m2. The density between stations was different with the highest at station II and the lowest at station I. The asymptotic length (L∞) of Margaritifera sp reached 126.97 mm for females and 121.42 mm for males.Keywords: Morphometric, Growth Pattern, Density, Margaritifera sp